KONTRIBUSI WORKSHOP PMRI TERHADAP KOMPETENSI GURU DALAM PEMBELAJARAN MATEMATIKA DI KELAS I SD NEGERI PERCOBAAN PADANG TAHUN PELAJARAN 2010/2011 - CESARIA S.Pd, ANNA (Jurnal Pelangi : Research of Education and Development, 2011)
Teacher’s competence is very influential on the mathemathics instructionin class. Therefore teacher’s competence should be improved and developedthrough a sustainable activity. One way to improve teacher competence is byholding Indonesian Realistic Mathematics Education workshops (RME). Thisstudy uses qualitative research methods with descriptive approach. This researchwas conducted in SD Negeri Percobaan Padang. The results of data analysisshowed that: (1) the competence of teachers in planning and carrying out thelearning process with RME approach has also been increased by using the RMEworkshop. This increase is due to a continuous process of workshop, (2) theobstacles faced in the planning and carrying out the learning process with RMEapproach significantly is planning and using media of instruction mathematicsappropriate with mathematics subject matter. The obstacle was minimized bydiscussion and simulation at the workshop.